2008
DOI: 10.5194/angeo-26-2795-2008
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences in polar mesosphere summer echoes observed in the Arctic and Antarctica

Abstract: Abstract. Polar Mesosphere Summer Echoes (PMSE) have been observed in the high latitudes of the Northern and Southern Hemisphere for several years using VHF radars located at Andenes/Norway (69 • N, 16 • E), Resolute Bay/Canada (75 • N, 95 • W), and Davis/Antarctica (69 • S, 78 • E). The VHF radars at the three sites were calibrated using the same methods (noise source and delayed transmitting signal) and identical equipment. Volume reflectivity was derived from the calibrated echo power and the characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 32 publications
(36 reference statements)
6
50
0
Order By: Relevance
“…This seemed to be consistent with the (limited) information then available, suggesting that summer mesopause temperatures at about 70 • latitude were about the same in both hemispheres (Lübken et al, 1999). Nilsson et al (2008) compared PMSE between Wasa and Davis, Antarctica (69 • S, 78 • E), and found about half the occurrence rates at Davis compared to Wasa, which was consistent with satellite indications of temperature differences at the time of those measurements between 69 • S and 73 • S. Latteck et al (2008) , and found occurrence rates of 18 %, 83 % and 38 %, respectively, with mean and maximum reflectivities also varying in the same order. For the same time interval, and the same detection threshold, Smirnova et al (2010) found about a 75 % occurrence rate at Kiruna, which gives a consistent difference between Andenes/Kiruna/Wasa (all about the same) and Davis.…”
supporting
confidence: 71%
“…This seemed to be consistent with the (limited) information then available, suggesting that summer mesopause temperatures at about 70 • latitude were about the same in both hemispheres (Lübken et al, 1999). Nilsson et al (2008) compared PMSE between Wasa and Davis, Antarctica (69 • S, 78 • E), and found about half the occurrence rates at Davis compared to Wasa, which was consistent with satellite indications of temperature differences at the time of those measurements between 69 • S and 73 • S. Latteck et al (2008) , and found occurrence rates of 18 %, 83 % and 38 %, respectively, with mean and maximum reflectivities also varying in the same order. For the same time interval, and the same detection threshold, Smirnova et al (2010) found about a 75 % occurrence rate at Kiruna, which gives a consistent difference between Andenes/Kiruna/Wasa (all about the same) and Davis.…”
supporting
confidence: 71%
“…Figure 3 shows a height-time intensity plot of radar volume reflectivity observed by the vertical beam of MAARSY. The volume reflectivity was converted directly from the absolute value of the received signal power as described in Latteck et al (2008). The vertical magenta line marks the WADIS-1 launch time when MAARSY was detecting a double-layered structure.…”
Section: Launch Conditionsmentioning
confidence: 99%
“…A detailed list of the experimental parameters is given in Table 1. In addition to these standard meteor experiments both radars were calibrated using the delay line method (Latteck et al, 2008). This permits to directly quantify the observed electron line densities in order to estimate the meteoroid size/mass assuming single body meteor ablation.…”
Section: Radarsmentioning
confidence: 99%